2009
DOI: 10.1007/s00415-009-5399-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation studies of the Portuguese experimental version of the Montreal Cognitive Assessment (MoCA): confirmatory factor analysis

Abstract: The Montreal Cognitive Assessment (MoCA) is a cognitive screening instrument created with the purpose of overcoming some of the insufficiencies of the Mini-Mental State Examination (MMSE). The MoCA evaluates more cognitive areas and is comprised of more complex tasks as compared with the MMSE, which makes it a more sensitive instrument in the detection of Mild Cognitive Impairment (MCI), a state that often progresses to dementia. In this study we performed an analysis of the psychometric and diagnostic propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
4
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 27 publications
7
73
4
6
Order By: Relevance
“…32 La MoCA, como instrumento cognitivo de tamizaje, mostró una adecuada validez concurrente al ser comparada tanto con los puntajes obtenidos con el MMSE como con la gravedad global observada en la sintomatología cognitiva evaluada por la PANSS, lo que es consistente con lo reportado en otros estudios. [33][34][35] La gravedad del cuadro sindromá-tico en los pacientes no es estable a lo largo del tiempo, por lo que aun cuando se observa una adecuada validez concurrente de la MoCA con la subescala cognitiva de la PANSS, será necesario determinar si ésta, al igual que la PANSS, es sensible a los probables cambios cognitivos observados a lo largo del padecimiento.…”
Section: Discussionunclassified
“…32 La MoCA, como instrumento cognitivo de tamizaje, mostró una adecuada validez concurrente al ser comparada tanto con los puntajes obtenidos con el MMSE como con la gravedad global observada en la sintomatología cognitiva evaluada por la PANSS, lo que es consistente con lo reportado en otros estudios. [33][34][35] La gravedad del cuadro sindromá-tico en los pacientes no es estable a lo largo del tiempo, por lo que aun cuando se observa una adecuada validez concurrente de la MoCA con la subescala cognitiva de la PANSS, será necesario determinar si ésta, al igual que la PANSS, es sensible a los probables cambios cognitivos observados a lo largo del padecimiento.…”
Section: Discussionunclassified
“…The MoCA (Montreal Cognitive Assessment) is a brief cognitive test specifically developed to screen for mild cognitive deficits and has been regarded as a suitable test for initial workup of subjects with suspected MCI. 38,39 It has been translated to and validated in European Portuguese 40 and Brazilian Portuguese, 41 but further studies are still needed to assess its potential as a screening tool for MCI in our population, particularly among less educated samples. Another interesting assessment strategy is the use of computer-based cognitive tests.…”
Section: Epidemiological Characteristics Of MCI In the Elderlymentioning
confidence: 99%
“…However, factor analyses of the MoCA have demonstrated that domains may be grouped differently (e.g., Duro, Simões, Ponciano, & Santana, 2010;Freitas et al, 2012). Given the multi-process nature of neuropsychological tasks, whereby any single task may tap into a range of perceptual, cognitive and motor abilities, and the overlapping nature of the cognitive domains assessed by the MoCA (Freitas et al, 2012), we created an additional score for analysis of executive function.…”
Section: Discussionmentioning
confidence: 99%